The Environment and its Protection in Light of Islamic Law (An Analytical Study) - Mustafa, Asst.Prof.Dr.Mohamed Khaled Mustafa; Suleiman, Asst.Prof. Dr. Abbas Ali Suleiman (Sulaimani Journal for Humanities, 2025)
Primitive man feared the environment and nature. Today, the environment fears humans. If we browse the pages of history, we find throughout history and across time the role of humans in polluting the environment, especially the great and industrialized nations. At the same time, authorities and rulers have played a role in environmental pollution due to wars and disasters, especially in our present era. This is due to the lack of rule of law over their companies and factories. In addition, car import companies, where most capitals of Islamic and Arab countries suffer from traffic congestion due to the massive number of cars and factories, are also involved. Preserving and protecting the environment is directly related to the awareness of the individual and the authorities, as well as to the individual's faith and national and ethnic affiliation. A religiously committed and aware individual, along with an aware authority, cares for the environment. Based on this great importance of the environment in every era and time, Islam came with legislation that reflects the status of man and his surrounding environment. God Almighty said: “And We have certainly honored the children of Adam and carried them on the land and sea and provided for them of the good things and preferred them over much of what We have created, with [definite] preference.” Islam did not create man in vain, but rather created him for specific goals and purposes - namely, to develop and colonize the earth - and these goals cannot be achieved by practicing acts of worship such as prayer, fasting, and Hajj alone without understanding its objectives. God Almighty said: “And remember when your Lord said to the angels, ‘Indeed, I am going to place a successive authority on earth.’” (Al-Baqarah: 30) And God Almighty said: “And do not commit abuse on the earth, spreading corruption.” (Al-Baqarah: 60) And God Almighty said: “And do not cause corruption on the earth after its reformation. And invoke Him in fear and hope. Indeed, the mercy of God is near to the doers of good.” (Al-A’raf: 56) And God Almighty said: God Almighty says: "And cooperate in righteousness and piety, but do not cooperate in sin and aggression. And fear Allah; indeed, Allah is severe in penalty." (Al-Ma'idah: 2). Based on the above, we decided to participate in your upcoming conference on this issue with a research paper on this topic. The research is titled "The Environment and Its Protection in Light of Islamic Law/An Analytical Study." Its nature required dividing it into sections as follows: Section One: Definition of the environment, its elements, and types in Islamic law. Section Two: Islam's concern for the environment, manifestations of its protection and improvement, and methods for preserving it. Section Three: Improving the environment and methods for preserving it in light of Islamic law